Masificación de la natación durante el tiempo de ocio como medida preventiva para evitar el sedentarismo en los alumnos del octavo año de educación general básica del colegio nacional Nueve de Octubre de la ciudad de Machala en el año lectivo 2013. - Centeno Pinta, Reminton Rubén (2015)
The massification of swimming is very important and much more taking it as a means to avoid a sedentary lifestyle among students and therefore the use of best free time, this research on the theme: MASSIFICATION SWIMMING DURING LEISURE TIME AS PREVENTIVE MEASURE tO AVOID sEDENTARISM STUDENTS iN EIGHTH YEAR oF BASIC EDUCATION GENERAL NATIONAL SCHOOL OCTOBER NINE CITY MACHALA in the school year 2013, it is divided into six chapters distributed as follows.